Higher serum follistatin levels are associated with increased vascular calcification in haemodialysis patients - Liu, Conghui; Zhang, Aihua; Li, Zhongxin (Frontiers in Endocrinology, 2026)
IntroductionFollistatin is a secreted protein whose main role is antagonizing the activity of transforming growth factor β (TGF-β) superfamily members. Our study aimed to evaluate the serum follistatin levels and establish their relationship with vascular calcification (VC) in haemodialysis (HD) patients.MethodsIn total, 206 HD patients and 41 healthy individuals, as controls, were included. Serum concentrations of follistatin, along with various clinical and laboratory parameters, were analyzed and compared. VC was assessed using the abdominal aortic calcification (AAC) scores. HD patients were categorized into a low-AAC-score group (AAC score < 4) and a high-AAC-score group (AAC score ≥ 4).ResultsHD patients had higher serum follistatin levels than the controls (1.25 ± 0.53 ng/ml vs. 0.88 ± 0.30 ng/ml, p < 0.001). Compared with the low-AAC-score group, the high-AAC-score group had a higher serum follistatin concentration (1.37 ± 0.57 ng/ml vs. 1.12 ± 0.46 ng/ml, p < 0.001). Multivariate logistic regression revealed that the higher serum follistatin, pulse pressure, serum total cholesterol (TC), serum sodium, and serum corrected calcium were significant independent determinants of high AAC scores of HD patients.ConclusionThe results herein provide the first clinical evidence of the association between serum follistatin and VC in HD patients. Higher follistatin, pulse pressure, serum corrected calcium levels, and lower serum sodium and TC levels are independent associated with high AAC scores in HD patients.